PENGARUH TAX AMNESTY TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA BANJARMASIN - rakhmi - ridhawati; - soedjatmiko; Aulia Rakhmi (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2020)
The purpose of this research is to empirical evidence the effect of tax amnesty on individual taxpayer compliance at KPP Pratama Banjarmasin. The method used in this research is quantitative method, with a total sample of 216 respondents consisting of personal taxpayers who take advantage of tax amnesty. The results of this study indicate that Tax Amnesty has an effect on the recommendation of individual taxpayers at KPP Pratama Banjarmasin because tax amnesty provides an opportunity for non-compliant individual taxpayers to comply because taxpayers who are given tax amnesty in the form of taxes that should not be owed are not subject to liability. administration of taxation and criminal sanctions in the field of taxation. Keywords: Tax amnesty, Taxpayer compliance